ANALISIS TITIK PULANG POKOK USAHA DAMPO PISANG PADAI NDUSTRI DIANA DI KOTA PALU - Saputra, Teguh; Antara, Made; Sulaeman, Sulaeman (AGROTEKBIS, 2018)
Diana industry is an small busnines which has develop in palu city. Industry Diana is engaget in agro-industrythat process agricultural commodities such as banana into dampo pisang.Industry Diana is located at.Jln Dayo Dara street, Palu central sulawesi. It sell the product at Katini street. The objective of this research was to know the total product, receiving and income from dampo pisang that the business reach break even point. The results of the analysis of break-even point dampo pisang production cost with sell on box show theresult as follows ; box (350 g) reaching at 130 box which sales Rp 25,000/box. The total cost that Diana industry used was Rp 3,250,000 and the income form the product was Rp 3,250,000.The result of break even point analysis of banana dampok of Mica box (400 gram) reacing at 177 boxes which was sale Rp 20,000/box. The total cost used was Rp 3,540,000, and the income from the product was Rp 3,540,000. Keywords: Break Even Point, Dampo Banana, Industry Diana.